Study of Some Biochemical Parameters in Iraqi Male Children with Thalassemia - H. K. Al-Hakeim; T. Al-Madani; M. M. R. Mahammad; D. A. Kateb; S. A. Nassir; S. Kareem (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
Thalassemia is a term that refers to a group of genetic disorders characterized by a defect in the synthesis of hemoglobin. It is sometimes called Mediterranean anemia. Many biochemical changes in the blood accompany this disease. In this research, some biochemical parameters were measured in thalassemic patients and compared with healthy control group. These parameters include serum Iron, ferritin, TIBC, hemoglobin, uric acid, albumin, calcium, transferrin, and transferrin saturation percentage.  The results of the research showed that there is a significant increase (P<0.05)  in serum iron and ferritin in thalassemic patients group in comparison with healthy control group. A significant decrease (P<0.05) in serum uric acid, TIBC, transferrin protein concentration, and hemoglobin. There is no significant difference (P>0.05) in serum albumin and calcium in both groups.           The results of this research can be explained by different mechanisms involving the hemolysis of erythrocytes and consequence precipitation of iron in the tissues. In addition, the hypoxia may be one of the reasons about the biochemical changes in thalassemic patients. Monitoring the measured parameters may be useful in the prognosis and follow up of the thalassemic patients.